Persepsi Mahasiswa Tingkat III Tentang Faktor-Faktor Yang Mempengaruhi Caring Behavior - Mestiana Br. Karo; Lindawati F. Tampubolon; Yeri nibenia zega (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2023)
Caring is a universal phenomenon that affects the way of thinking, feeling, and behaving for every individual when having a relationship or communicating with others. Caring behavior in the collective is explicitly an essential human reflection which is manifested through the attributes of affection, competence, self-confidence, conscience, and commitment, because caring behavior is very important in interacting with others. The purpose of the study is to identify and identify the third-level student's perception of the factors that influence caring behavior including individual factors, psychological factors, and organizational factors. The researcher used a descriptive research design with a sample of 85 people. The sampling technique used is total sampling. The research instrument used a student caring behavior questionnaire with 21 questions distributed via google from. The results show that there were 39 students (45.9%) who agreed to agree and a minority strongly disagreed with 2 students (2.4%), psychological factors agreed to 46 students (54.1%) and a minority strongly disagreed as much as 1 student (1.2%), organizational factors which majority agree 45 students (52.9%) and minority strongly disagree as much as 1 student (1.2%). It is hoped that the results of this study will increase awareness in carrying out caring behavior with good communication to create better caring behavior. Further researchers can conduct research methods with interviews in order to be able to observe directly about the perception of the factors that influence caring behavior.